Eye-Tracking - Gabriela GROSSECK (Informatică economică, 2006)
Eye-tracking: one of the newest and most efficient methods of improving on-line marketing communication is called eye-tracking. Marketers have borrowed this technique, usually used in psychological and medical research, in order to study web users with the help of a video camera incorporated in the monitor.